Delphi/AHP-Based Method for Biomass Sustainable Assessment in the Sugar Industry - (:unkn) unknown (MDPI, 2024)
Multi-criteria methods are highly attractive tools to address the inherent complexity of evaluating problems in various scientific areas. The combination of methods such as Delphi/AHP is emerging as a robust alternative to evaluate the sustainability of ...
Keywords: Biomasa; Industria azucarera